Single-phase-to-ground fault model analysis of arc suppression coil grounding system in distribution network. Issue 1 (November 2020) - Xinyu, Zhang; Yu, Nie; Chuanzong, Zhao; Wei, Du; Yanan, Wang; Zimo, ZHENG
Abstract: Start your abstract here…The short-circuit fault type of China's medium-voltage distribution network is 80% single-phase ground fault. Since the non-effective grounding system can continue to operate for 1∼2 hours after single-phase-to-ground fault, the analysis of the single-phase-to-ground fault model is very necessary for the arc-suppression coil grounding mode in distribution network. In this paper, by establishing a single-phase ground fault model of the distribution network with arc-suppression coil grounding method, it is theoretically analysed that is the different transition resistances in metallic grounding, high-resistance grounding and intermediate state, and use ATP/EMTP simulation to analyse the fault occurrence, the change and difference of the current waveform on the fault line and the normal line as well as the arc suppression coil. It is concluded that when the single-phase ground fault occurs in the distribution network under the grounding mode of the arc suppression coil, no matter how the transition resistance changes, the current direction of the fault line and the normal line (when the predetermined reference direction is the bus flowing to lines) is reversed, but the difference between the fault current and the normal current is weakened with the change of the transition resistance, so different faults models should be used for different grounding resistances to analyse the transient currents of normal and fault lines on the zero sequence circuit model.